Pengaruh Nilai Tukar Rupiah Dan Jumlah Uang Beredar Terhadap Harga Saham Perusahaan Kalbe Farma Tbk Tahun 2014-2018 - Wahyu Ika Saputri (WADIAH, 2022)
The stock price of a company can show the performance of the company. Stock prices will be affected immediately by macroeconomic changes, because investors will calculate both positive and negative impacts on the company's performance and then take the current decision to buy or sell the shares in question. Therefore, stock prices adjust more quickly to changes in macroeconomic variables than the company's performance. The object of this research is the company Kalbe Farma Tbk which has been active and registered in the Jakarta Islamic Index in 2014-2018. The approach used in this study is a quantitative approach with the help of SPSS 21.0 software. The results of the research on the rupiah exchange rate variable (X_1) on stock prices show the results of the t test where the significant value of the rupiah exchange rate variable is 0.003 < (0.05) and the t arithmetic value is -3.136 < t table is -2.00247 which means The rupiah exchange rate has a negative effect on the stock price of Kalbe Farma Tbk. While the results of the research on the money supply variable (X〗_2) on stock prices show the results of the t-test t-test where the significant value of the money supply variable is 0.226 > (0.05) and the t-count value is 1.223 < t table of 2 .00247, which means that the money supply has no effect on the share price of Kalbe Farma Tbk. Keywords: Rupiah Exchange Rate, Money Supply, Stock Price